2020
DOI: 10.33603/jibm.v3i2.2513
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Perilaku Herding dan Volatilitas IHSG terhadap Return Pasar di Bursa Efek Indonesia

Abstract: This study aims to determine the influence of herding behavior and JCI volatility on market returns at Indonesia Stock Exchange during 2014-2018 period. This research applies quantitative research methods. The sample in this study was taken using a saturated sampling technique. The data in this study uses secondary data collected from various sources, such as the Indonesia Stock Exchange, Yahoo! Finance, Bloomberg and Reuters. This study uses multiple linear regression analysis to process data and test hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…Apart from that, the test results of this research strengthen the results of research conducted by Wijaya and Meirisa (2019), who found that negative information influences novice investors' investment decisions to follow stock price movements.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Apart from that, the test results of this research strengthen the results of research conducted by Wijaya and Meirisa (2019), who found that negative information influences novice investors' investment decisions to follow stock price movements.…”
Section: Resultssupporting
confidence: 82%
“…These abnormal profits are obtained by following the same price movements to gain fast profits. This is due to the fact that some information is not published to the general public, and only certain actors know about it (Wijaya & Meirisa, 2019). This aligns with the characteristics of novice investors who often expect high returns by trading shares that are widely traded, and their mastery of information is still not high due to a lack of funds to employ an analyst.…”
Section: Herding Behavior In Novice Investor Investmentsmentioning
confidence: 88%
See 1 more Smart Citation